On the Edge Sidi Larbi Cherkaoui's Foi - Sansom, Bruce (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Sidi Larbi Cherkaoui's Foi. PALABRAS CLAVE: Sidi Larbi Cherkaoui, contemporary dance, Foi, Spanish-sounding medieval music, contrasting situations.